Serological Confirmation of Chagas' Disease by a Recombinant and Peptide Antigen Line Immunoassay: INNO-LIA Chagas - Saez-Alquézar, Amadeo (American Society for Microbiology, 2000)
Although screening for Trypanosoma cruzi antibodies is mandatory in most South American countries, current tests are insensitive and have poor specificity. A recently optimized line immunoassay (the INNO-LIA Chagas assay) for the serological confirmation of Chagas' disease was evaluated at a large blood bank in São Paulo, Brazil. Sera from blood donors who reacted in at least one of three serological screening assays (n = 1,604) and who returned for a follow-up were retested, and the donors were interviewed to assess their epidemiological risk. The results obtained by the confirmatory assay evaluated in this study were compared to those obtained by the three different screening assays. Upon consideration of the consensus results obtained by the three different screening assays as a “gold standard,” the INNO-LIA Chagas assay showed a sensitivity of 99.4% (95% confidence interval [CI], 98.3 to 99.9) and a specificity of 98.1% (95% CI, 96.6 to 99.0) for positive (n = 503) and negative (n = 577) sera. The INNO-LIA Chagas assay confirmed the results for significantly larger numbers of positive samples of at-risk individuals independent of the number of positive screening tests (P = 0.017, Mantel-Haenszel test). In conclusion, the INNO-LIA Chagas assay reliably confirmed the presence of antibodies to T. cruzi and can be implemented as a confirmatory assay for Chagas' disease serology.